2007
DOI: 10.1002/ajhb.20660
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on infant weight and weight change: The Fels longitudinal study

Abstract: Despite significant progress in understanding the mechanisms by which the prenatal/maternal environment can alter development and adult health, genetic influences on normal variation in growth are little understood. This work examines genetic and nongenetic contributions to body weight and weight change during infancy and the relationships between weight change and adult body composition. The dataset included 501 white infants in 164 nuclear and extended families in the Fels Longitudinal Study, each with 10 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
61
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(70 citation statements)
references
References 50 publications
7
61
0
2
Order By: Relevance
“…Genes with pleiotropic effects could lead to genetic correlations between infancy growth and adult outcomes, as shown for other traits (44). Although there is evidence for moderate heritability of early growth in well nourished populations (45,46), no heritability estimates have been calculated under conditions of nutritional stress and growth faltering, which were common in the Cebu cohort during infancy. Future studies should strive to incorporate analysis of growth-influencing genotypes (47), which could contribute to, or moderate, the associations we document.…”
Section: Discussionmentioning
confidence: 99%
“…Genes with pleiotropic effects could lead to genetic correlations between infancy growth and adult outcomes, as shown for other traits (44). Although there is evidence for moderate heritability of early growth in well nourished populations (45,46), no heritability estimates have been calculated under conditions of nutritional stress and growth faltering, which were common in the Cebu cohort during infancy. Future studies should strive to incorporate analysis of growth-influencing genotypes (47), which could contribute to, or moderate, the associations we document.…”
Section: Discussionmentioning
confidence: 99%
“…This is slightly higher than others previously reported. 7,14 The reason might lie in the very homogeneous set of infants, identified by applying stringent inclusion criteria. The identification of these factors, which yield a high estimate of heritability, makes them very useful in future research when looking for PWG-associated genes.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In particular, Spiegler et al, 8 who studied weight gain during the first weeks of life, reported a strong genetic influence on postnatal growth in preterm infants. Their case series included major diseases such as sepsis, intracranial hemorrhage, and bronchopulmonary dysplasia.…”
mentioning
confidence: 97%
“…5 Studies show that heredity is an important factor for childhood-onset obesity. 6,7 The largest study concerning the genetics of childhood obesity, where 5530 cases and 8318 controls were evaluated, showed a strong genetic influence in the development of childhood obesity. 8 The dopamine type-2 receptor (DRD2) gene contains 66.097 pb, it is located on chromosome 11 (q22-q23) and encodes the D2 subtype of the dopamine receptor, a transmembrane protein that couple to G-protein and inhibits adenylyl cyclase activity.…”
Section: Introductionmentioning
confidence: 99%